Peran Strategis SDM Dalam Transformasi Pertanian dan Pemberdayaan Komunitas Petani - Rangga Adi Wijaya (Universitas Muria Kudus, 2026)
The uncertainty of seasonal cycles, increasing frequency of extreme weather events, and production fluctuations are no longer merely ecological issues; they have become new arenas that affect the social structure and economic practices of farming communities. The circular economy program strategy for adaptive agricultural transformation creates space for a social transformation process involving human capacity building, changes in perspectives, and shifts in the structure of economic practices. In this context, HR (Human Resources) play a key role in promoting more resilient and sustainable farming practices. This research was conducted in a farming community assisted by the Trukajaya Christian Foundation in Bansari sub-district, Temanggung Regency. The study employed a descriptive qualitative method, with three main informants: the head of the Bansari farming group, GKJ Sindoro Church Council, and staff from Trukajaya Christian Foundation. Farmers concerns regarding climate change adaptation tend to prioritize technical management through the development of adaptive varieties, irrigation improvements, or increased production capacity. Due to a lack of knowledge among farmers, the transition to a circular and sustainable economy concept is limited. Therefore, promoting a circular economy in this farming community is part of an adaptive farming strategy to build farmer resilience in the face of climate change.